NEW 6-(3-INDOLYL)BENZO[B]CARBAZOLES - Mardi Santoso (Indonesian Journal of Pharmacy, 2001)
Some attempts have been carried out to synthesize polycyclic heterocyclic compounds derived from new benzocarbazoles (1). New 6-(3-indolyl)benzo[b]-carbazoles (2a) have been synthesised in good yields from the reaction of simple indoles and o-phthaldialdehid in methanol catalysed by p-toulenesulfonic acid monohydrate. Their precise structure were established by microanalysis, spectroscopy, and X-ray crystallography of the benzo[b]carbazole (2a).Keywords: indoles, polycyclic heterocyclic compounds, benzo[b]carbazoles